Comparison of experimental results with fem for velocity impact response behavior of laminated composite arches - Ayten, Ali İmran (My University, 2014)
Kompozit malzemeler darbe dayanımı, elastik modülü, çekme dayanımı gibi yüksek mekanik özelliklerinden dolayı önem kazanmıştır. Özellikle kompozitlerin darbe dayanımı ya da enerji emme kapasiteleri onları askeri ve savunma sanayisinde önemli kılmıştır. Aynı zamanda havacılık, denizcilik ve askeri sanayisi gibi ağırlık azaltılmasının önemli bir tasarım parametresi olduğu mühendislik uygulamalarında da kompozit malzemeler önem kazanmıştır. Bu tez çalışmasının amacı kompozit yapıların geometrik yüzeyinin kompozit malzemenin darbe dayanımı üzerindeki etkilerinin araştırılması ve kompozit numunelere uygulanan düşük hızlı darbe dayanımı testinin sonuçları ile numerik sonuçların kıyaslanmasıdır. Elde edilen sonuçlar özellikle askeri amaçlar olmak üzere farklı alanlarda da kullanılabileceğinden önem taşımaktadır. Çalışmada kullanılan numuneler silindirik, eliptik ve küresel olmak üzere üç farklı geometride üretilmiştir. Her bir numune grubu 5, 10, 15 mm. olmak üzere üç farklı yüksekliğe sahiptir. Düşük hızlı darbe testi her bir numuneye üç kez uygulanmıştır.

Composite materials have been become important material due to they have high mechanical properties such as impact resistance, elasticity modulus, tensile strength etc. Especially impact resistance or energy absorption capability properties of composite materials have a vital importance in military and defense industry. They also have been gained significance in many different engineering applications like military, naval industry and especially in aerospace, where weight reduction is one of the most important design parameters. The objective of this thesis study is investigate to effect of geometric shape of composite structures on impact resistance of composite materials and compare to numerical and experimental data of low velocity impact test on composite samples. The results to obtain are important because they can be used different field especially military purposes. Specimens which having three different geometric shape such as cylindrical, elliptical, spherical have been manufactured in this study. Each of them has different height such as 5, 10, 15 mm. Low velocity impact test is applied to samples three times of each of them.
Keywords: Askeri_Silahlı Kuvvetler; Deniz; Hava; Kompozit Malzemeler; Makine; Makine Eğitimi; Metaller; Mühendislik